Risk Recognition and Sensation Seeking in Revictimization and Posttraumatic Stress Disorder. (January 2013) - Volkert, Jana; Randjbar, Sarah; Moritz, Steffen; Jelinek, Lena
Impaired risk recognition has been suggested to be associated with the risk for revictimization and the development of posttraumatic stress disorder (PTSD). Moreover, risk behavior has been linked to high sensation seeking, which may also increase the probability of revictimization. A newly designed behavioral experiment with five audiotaped risk scenarios was used to investigate risk recognition in revictimized, single-victimized, and nontraumatized individuals with and without PTSD. Moreover, the potential role of sensation seeking in revictimization, and PTSD as well as its relation to risk recognition was explored. Revictimized, single-victimized, and nontraumatized individuals did not differ with regard to general risk recognition. However, delayed risk recognition was found for the revictimized group when arousal ratings were considered. No differences in sensation seeking were found between the three groups; only the nontraumatized group showed lower boredom susceptibility relative to the revictimized group. Delayed risk recognition was associated with high sensation seeking. Furthermore, PTSD symptoms significantly predicted exit levels of risk scenarios. Findings are discussed against the background of previous research.